Damage and corrosion of conductive asphalt concrete subjected to freeze–thaw cycles and salt. (July 2013) - Tang, N.; Sun, C. J.; Huang, S. X.; Wu, S. P.
Abstract : Freeze–thaw cycles and salt become the main reasons for the deterioration of road properties in the frozen coastal regions. Conductive asphalt concrete (CAC) is a new functional asphalt concrete that can be used for self-monitoring or snow melting with smart characteristics. The complex corrosion of freeze–thaw cycles and salt on strength, air voids, weight and crack of CAC was investigated through freeze–thaw tests. Test results indicate that freeze–thaw cycles and salinity are main factors having an influence on CAC. Salt has a significant effect on the performance of CAC.